Assessment of grain protein composition in old and modern Italian durum wheat genotypes - De Santis, Michele A.; Giuliani, Marcella M.; Giuzio, Luigia; De Vita, Pasquale; Flagella, Zina (Italian Journal of Agronomy, 2018)
The effect of durum wheat breeding on technological quality was mainly investigated in relation to allelic polymorphism, in particular for glutenins, while fewer information are available on the changes in grain protein proportion. In the present investigation, an old and a modern group of durum wheat genotypes, grown in Mediterranean environment, were evaluated for grain protein composition, according to Osborne extraction procedure. In modern genotypes, a higher relative content of soluble glutenin was observed which might contribute to their better technological performance. Moreover, a slight decrease both in the amount of gliadin fraction, mainly responsible for gluten related disorders, and in the monomeric to polymeric protein ratio was observed in the modern durum wheat varieties. Among the genotypes investigated, Svevo and Saragolla, showed the lowest gliadin and the highest glutenin content, while the old genotypes Cappelli showed an opposite behaviour.